An assessment of gas power leakage and frictional losses from the top compression ring of internal combustion engines. (February 2020) - Turnbull, R.; Dolatabadi, N.; Rahmani, R.; Rahnejat, H.
Abstract: A multi-physics integrated analysis of piston top compression ring of a high-performance internal combustion engines is presented. The effects of transient ring elastodynamics, thermal gas flow through piston crevices upon chamber leakage pressure and parasitic frictional losses are investigated. The multi-physics analysis comprises integrated flexible ring dynamics, ring-liner thermo-mixed hydrodynamics and gas blow-by, an approach not hitherto reported in literature. The predictions show close conformance to frictional measurements under engine motored dynamometric conditions. It is shown that power losses due to gas leakage can be as much as 6 times larger than frictional losses, which are usually considered as the main sources of inefficiency. Highlights: Integrated predictive multi-physics, multi-scale analysis of IC engine piston compression losses. The effect of transient ring elastodynamics and combustion gas blow-by on generated conjunctional friction. Verified predictions with dynamometric engine frictional measurements. Gas leakage power losses due to blow-by can exceed frictional losses by as much as 6 times due to ring elastodynamics.